Seeded on-surface supramolecular growth for large area conductive donor-acceptor assembly - Goudappagouda; Chithiravel, Sundaresan; Krishnamoorthy, Kothandam; Gosavi, Suresh W.; Babu, Sukumaran Santhosh (Chemical Communications, 2015)
Charge transport features of organic semiconductor assemblies are of paramount importance. However, large-area extended supramolecular structures of donor-acceptor combinations with controlled self-assembly pathways are hardly accessible. In this context, as a representative example, seeded on-surface supramolecular growth of tetrathiafulvalene and tetracyano-p-quinodimethane (TTF-TCNQ) using active termini of solution-formed sheaves has been introduced to form an extended assembly. We demonstrate for the first time, the creation of a large-area donor-acceptor assembly on the surface, which is practically very tedious, using a seeded, evaporation-assisted growth process. The excellent molecular ordering in this assembly is substantiated by its good electrical conductivity (similar to 10(-2) S cm(-1)). The on-surface assembly via both internally formed and externally added sheaf-like seeds open new pathways in supramolecular chemistry and device applications.

Cascade energy transfer and tunable emission from nanosheet hybrids: locating acceptor molecules through chiral doping - Goudappagouda; Wakchaure, Vivek Chandrakant; Ranjeesh, Kayaramkodath Chandran; Abhai, Chalona Antony Ralph; Babu, Sukumaran Santhosh (Chemical Communications, 2017)
Light harvesting donor-acceptor assemblies are indispensable to efficiently tap photons. In an attempt to improve the light harvesting efficiency of an acceptor doped assembly, we design and synthesize a donor-acceptor-donor triad which exhibits an exceptional intramolecular energy transfer with excellent efficiency. Moreover, a facile cascade energy transfer (energy funnelling) is observed in the presence of a series of second acceptors (63-91% efficiency) with tunable emission colours. Self-assembled nanosheets formed by the triad in the presence of acceptors exhibit cascade energy transfer assisted tunable emission. In addition, use of chiral acceptors induces chirality to the triad and results in the formation of chiral nanosheets alongwith cascade energy transfer. Here chiral induction, nanosheet formation and cascade energy transfer in the presence of chiral acceptors are used as tools to probe the intercalation of acceptor molecules in the donor scaffold.

Mixed-stack charge transfer crystals of pillar[5]quinone and tetrathiafulvalene exhibiting ferroelectric features - Shivakumar, Kilingaru I.; Swathi, Kadaba; Goudappagouda; Das, Tamal C.; Kumar, Ashwani; Makde, Ravindra D.; Vanka, Kumar; Narayan, Kavassery S.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemistry- A European Journal, 2017)
Ferroelectric materials find extensive applications in the fabrication of compact memory devices and ultra-sensitive multifunctional detectors. Face-to-face alternate stacking of electron donors and acceptors effectuate long-range unidirectional ordering of charge-transfer (CT) dipoles, promising tunable ferroelectricity. Herein we report a new TTF-quinone system-an emerald green CT complex consisting pillar[5]quinone (P5Q) and tetrathiafulvalene (TTF). The CT crystals, as determined by single crystal synchrotron X-ray diffraction, adopt a 1:1 mixed-stack arrangement of donor and acceptor with alternating dimers of TTF and 1,4-dioxane encapsulated P5Q. The TTF-P5Q.dioxane crystal possesses a macroscopic polarization axis giving rise to ferroelectricity at room temperature. The CT complex manifests ferroelectric features such as optical polarization rotation, temperature-dependent phase transition and piezoelectric response in single crystals. Ferroelectric behavior observed in P5Q-based CT complex widens the scope for further work on this structurally intriguing and readily accessible cyclic pentaquinone.
Keywords: Acceptor; Charge-transfer complexes; Chemistry; Conductors; DDQ; Donor; ferroelectric; Macrocycles; Organic Metals; Pi-interaction; Pillar[5]quinone; salts; Transfer Complexes; Transport

Mechano-responsive room temperature luminescence variations of boron conjugated pyrene in air - Wakchaure, Vivek C.; Ranjeesh, Kayaramkodath C.; Goudappagouda; Das, Tamal; Vanka, Kumar; Gonnade, Rajesh; Babu, Sukumaran S. (Chemical Communications, 2018)
Stimuli responsive tunable luminescence is a promising field of research. Even though mechanofluorescence is widely studied, mechanophosphorescence remains unexplored. Here we report the mechano-driven fluorescence and phosphorescence variations of a pyrene tetraboronic ester derivative. The fluorochromic and room temperature phosphorescence features are supported by theoretical studies and single crystal analysis. The mechanically ground fluorescence active but phosphorescence inactive pyrene tetraboronic ester exhibits room temperature phosphorescence in air withmechanical force. The efficient intermolecular electronic coupling in the dimer formed upon scratching enables a good communication between singlet and triplet states, hence resulting in room temperature mechanophosphorescence.

One‐dimensional porphyrin‐fullerene (C60) assemblies: role of central metal ion in enhancing ambipolar mobility - Goudappagouda; Gedda, Murali; Kulkarni, Giridhar U.; Sukumaran, Santhosh Babu (Chemistry - A European Journal, 2018)
One-dimensional (1D) nanostructures of -conjugated molecules exhibiting excellent charge carrier mobilities have found much interest in organic electronic devices. Even though it is tedious to form such structures, the availability of highly delocalized electron and hole carriers in these donor (D)-acceptor (A) co-assemblies realize ambipolar charge transport. Here we report the successful demonstration of a simple solution casting method to create ambipolar donor-acceptor single crystalline assembly. 1D assemblies of 5,10,15,20-tetraphenylporphyrins (H2TPP, ZnTPP) and fullerene (C60) exhibit high ambipolar mobility in the range of 0.8-3.4 cm2/Vs for electrons and holes with high ON/OFF ratio and low threshold voltage. A direct experimental proof for the pivotal role of central Zn2+ in tetraphenyl porphyrin, which enables a strong D-A charge transfer interaction in the cocrystal and thereby induces electron (1.35 cm2/Vs), hole (3.42 cm2/Vs) mobilities, the highest reported for two component D-A assemblies using solution casting, is demonstrated.

Cascade energy transfer and tunable emission from nanosheet hybrids: locating acceptor molecules through chiral doping (vol 53, pg 7072, 2017) - Goudappagouda; Wakchaure, Vivek Chandrakant; Ranjeesh, Kayaramkodath Chandran; Abhai, Chalona Antony Ralph; Babu, Sukumaran Santhosh (Chemical Communications, 2019)
Correction for `Cascade energy transfer and tunable emission from nanosheet hybrids: locating acceptor molecules through chiral doping' by Goudappagouda et al., Chem. Commun., 2017, 53, 7072-7075.

Charge transfer liquid: a stable donor-acceptor interaction in the solvent-free liquid state - Wakchaure, Vivek Chandrakant; Pillai, Lekshmi, V; Goudappagouda; Ranjeesh, Kayaramkodath Chandran; Chakrabarty, Suman; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R; Babu, Sukumaran Santhosh (Chemical Communications, 2019)
Charge-transfer complexes have been an inspiration to develop many functional soft materials. However, most of those studies have focused on solution based assemblies wherein the explicit control of solvents and their polarity are crucial. In this context, we explore an efficient and stable charge transfer liquid using a solvent-free liquid dialkoxynaphthalene donor and a naphthalenediimide acceptor. It has been observed that irrespective of the donor-acceptor ratio, the charge-transfer liquid exhibited an unprecedented stability and retained characteristic features even at increased temperatures. The underlying intermolecular interactions leading to efficient CT have been examined by NMR techniques together with theoretical modelling studies. The concept of charge transfer liquid will be highly beneficial for the development of processable optoelectronically active materials.

Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule (vol 54, pg 212, 2018) - Shivakumar, Kilingaru I.; Goudappagouda; Gonnade, Rajesh G.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemical Communications, 2019)
Correction for `Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule' by Kilingaru I. Shivakumar et al., Chem. Commun., 2018, 54, 212-215.

Imidazole-linked crystalline two-dimensional polymer with ultrahigh proton-conductivity - Ranjeesh, Kayaramkodath Chandran; Ilathvalappil, Rajith; Veer, Sairam Dnyaneshwar; Peter, Joseph; Wakchaure, Vivek Chandrakant; Goudappagouda; Raj, K. Vipin; Kurungot, Sreekumar; Babu, Sukumaran Santhosh (Journal of the American Chemical Society, 2019)
Proton-exchange membrane fuel cells are promising energy devices for a sustainable future due to green features, high power density, and mild operating conditions. A facile proton-conducting membrane plays a pivotal role to boost the efficiency of fuel cells, and hence focused research in this area is highly desirable. Major issues associated with the successful example of Nafion resulted in the search for alternate proton conducting materials. Even though proton carrier loaded crystalline porous organic frameworks have been used for protonconduction, the weak host-guest interactions limited their practical use. Herein, we developed a crystalline 2D-polymer composed of benzimidazole units as the integral part, prepared by the condensation of aryl acid and diamine in polyphosphoric acid medium. The imidazole linked-2D-polymer exhibits ultrahigh proton conductivity (3.2 X 10(-2) S cm(-1)) (at 95% relative humidity and 95 degrees C) in the pristine state, which is highest among the undoped porous organic frameworks so far reported. The present strategy of a crystalline proton-conducting 2D-polymer will lead to the development of new high performing crystalline solid proton conductor.

Paintable room-temperature phosphorescent liquid formulations of alkylated bromonaphthalimide - Goudappagouda; Manthanath, A.; Wakchaure, V. C.; Ranjeesh, K. C.; Das, T.; Vanka, K.; Nakanishi, T.; Babu, S. S. (Angewandte Chemie - International Edition, 2019)
Organic phosphors have been widely explored with an understanding that crystalline molecular ordering is a requisite for enhanced intersystem crossing. In this context, we explored the room‐temperature phosphorescence features of a solvent‐free organic liquid phosphor in air. While alkyl chain substitution varied the physical states of the bromonaphthalimides, the phosphorescence remained unaltered for the solvent‐free liquid in air. As the first report, a solvent‐free liquid of a long swallow‐tailed bromonaphthalimide exhibits room‐temperature phosphorescence in air. Doping of the phosphor with carbonyl guests resulted in enhanced phosphorescence, and hence a large‐area paintable phosphorescent liquid composite with improved lifetime and quantum yield was developed.

Squaraine-linked metalloporphyrin two-dimensional polymer photocatalyst for hydrogen and oxygen evolution reactions - Ranjeesh, K. C.; George, L.; Wakchaure, V. C.; Goudappagouda; Devi, R. N.; Babu, S. S. (Chemical Communications, 2019)
Efficient water splitting photocatalysts are an energetically demanding and cost-effective method for generating renewable energy. Significant research has been reported to advance this approach. However, the use of organic photocatalysts and the presence of residual catalysts trapped in the porous frameworks present major concerns about the efficiency of this strategy. Herein, we report the photocatalytic evolution of H2 and O2 by a multi-hydroxyl group-decorated metalloporphyrin-based two-dimensional catalyst developed via metal catalyst-free synthetic route. Though metalloporphyrins have long been used for catalytic functions, a heterogeneous photocatalyst delivering both H2 and O2 has not yet been realized. This polymer catalyst design enables the photocatalytic diatomic O2 release, a bottleneck in water splitting, in a facile way. Photocatalytic release of H2 as well as O2 occurs with long-term durability of 20 cycles in 300 days with negligible decrease in efficiency, thus demonstrating the excellent performance of this new catalyst.

Self-assembled helical arrays for the stabilization of the triplet state - Nidhankar, Aakash D.; Goudappagouda; Kumari, Divya S. Mohana; Chaubey, Shailendra Kumar; Nayak, Rashmi; Gonnade, Rajesh G.; Kumar, G. V. Pavan; Krishnan, Retheesh; Babu, Sukumaran Santhosh (Angewandte Chemie-International Edition, 2020)
Room-temperature phosphorescence of metal and heavy atom-free organic molecules has emerged as an area of great potential in recent years. A rational design played a critical role in controlling the molecular ordering to impart efficient intersystem crossing and stabilize the triplet state to achieve room-temperature ultralong phosphorescence. However, in most cases, the strategies to strengthen phosphorescence efficiency have resulted in a reduced lifetime, and the available nearly degenerate singlet-triplet energy levels impart a natural competition between delayed fluorescence and phosphorescence, with the former one having the advantage. Herein, an organic helical assembly supports the exhibition of an ultralong phosphorescence lifetime. In contrary to other molecules, 3,6-phenylmethanone functionalized 9-hexylcarbazole exhibits a remarkable improvement in phosphorescence lifetime (>4.1 s) and quantum yield (11 %) owing to an efficient molecular packing in the crystal state. A right-handed helical molecular array act as a trap and exhibits triplet exciton migration to support the exceptionally longer phosphorescence lifetime.
Keywords: carbazole; helicity; phenylmethanone; ultralong phosphorescence; waveguiding

Tuning phosphorescence features of triphenylamines by varying functional groups and intermolecular interactions - Goudappagouda; Asokan, Kiran; Nayak, Rashmi; Krishnan, Retheesh; Babu, Sukumaran Santhosh (Dyes and Pigments, 2020)
Organic room temperature phosphorescent materials are known for their synthetic feasibility, tunable phosphorescence wavelength and lifetime, etc. Hence new design strategies have been applied on various fluorophores to improve phosphorescence features. Among those, triphenylamines are phosphorescence active due to the presence of nitrogen atom, propeller molecular structure, and intermolecular interactions in the crystal state. Here we have studied the room temperature phosphorescence of a series of triphenylamines with various functional groups. Detailed studies have shown that the phosphorescence can be fine-tuned by functional group modification. A long phosphorescence lifetime around 100 ms at room temperature in air can be achieved by the interplay of intermolecular interactions, singlet-triplet energy gap and extent of intersystem crossing using functional group variation. Interestingly, an exciplex assisted ultralong phosphorescence lifetime (more than 20 times) is observed for a combination of triphenylamine and naphthalenemonoimide in air.
Keywords: Exciplex; fluorescence; Phosphorescence; triphenylamine

Aggregation-induced phosphorescence of an anthraquinone based emitter - Goudappagouda; Nidhankar, Aakash D.; Nayak, Rashmi A.; Babu, Sukumaran Santhosh (Organic & Biomolecular Chemistry, 2021)
Room temperature phosphorescence (RTP) of metal-free organic molecules is a hot topic of current research interest. RTP can be enhanced through aggregation, crystallization, and the support of polymers and host-guest assemblies. The characteristics of highly phosphorescent aggregates formed from conventional chromophores make them ideal candidates for many potential applications. In this direction, we focused on the aggregation-induced phosphorescence of an anthraquinone derivative AqC6 in solution and in crystal state. The weakly emissive dilute solution exhibits a tunable emission with enhanced intensity and room temperature phosphorescence by increasing the concentration and solvent-antisolvent combination. The enhanced phosphorescence of crystals has been recreated in the solution by making use of aggregation. Interestingly, the support of PMMA enabled AqC6 to achieve enhanced processability, phosphorescence lifetime (174 ms) and quantum yield (5%).

Efficient metal-free organic room temperature phosphors - Nidhankar, Aakash D.; Goudappagouda; Wakchaure, Vivek C.; Babu, Sukumaran Santhosh (Chemical Science, 2021)
An innovative transformation of organic luminescent materials in recent years has realised the exciting research area of ultralong room-temperature phosphorescence. Here the credit for the advancements goes to the rational design of new organic phosphors. The continuous effort in the area has yielded wide varieties of metal-free organic systems capable of extending the lifetime to several seconds under ambient conditions with high quantum yield and attractive afterglow properties. The various strategies adopted in the past decade to manipulate the fate of triplet excitons suggest a bright future for this class of materials. To analyze the underlying processes in detail, we have chosen high performing organic triplet emitters that utilized the best possible ways to achieve a lifetime above one second along with impressive quantum yield and afterglow properties. Such a case study describing different classes of metal-free organic phosphors and strategies adopted for the efficient management of triplet excitons will stimulate the development of better candidates for futuristic applications. This Perspective discusses the phosphorescence features of single- and multi-component crystalline assemblies, host-guest assemblies, polymers, and polymer-based systems under various classes of molecules. The various applications of the organic phosphors, along with future perspectives, are also highlighted.

Excimer to exciplex transition through realization of donor-acceptor interactions in luminescent solvent-free liquids - Wakchaure, Vivek Chandrakant; Goudappagouda; Das, Tamal; Ravindranathan, Sapna; Babu, Sukumaran Santhosh (Nanoscale, 2021)
Luminescent solvent-free organic liquids are known for their enhanced quantum yield, color tunability, and availability of a matrix for other dopants to generate hybrid luminescent materials with improved features for newer applications. Herein, we report a donor-acceptor based luminescent ``exciplex liquid'' by utilizing the slightly different electron affinity of the acceptor molecules. A red-shifted broad exciplex emission exhibited by the donor-acceptor pair even at a lower concentration of the acceptor (0.001 equiv.) indicates high efficiency in the solvent-free state. A detailed NMR study revealed weak intermolecular interactions between the donor and acceptor in the solvent-free matrix that stabilizes the exciplex liquid. The failure of structurally similar solid counterparts to form an exciplex confirms the advantage of the available supportive liquid matrix. Besides, the luminescent exciplex liquid is found efficient in sensing application, which is unachievable by either the individual liquids or their solid counterparts. Here, a transition of a donor-acceptor pair from a solid to solvent-free liquid results in a new hybrid liquid that can be an alternative for solid sensor materials.

Donor-acceptor based solvent-free organic liquid hybrids with exciplex emission and room temperature phosphorescence - Wakchaure, Vivek Chandrakant; Veer, Sairam D.; Nidhankar, Aakash D.; Goudappagouda; Nayak, Rashmi; Asokan, Kiran; Ravindranathan, Sapna; Babu, Sukumaran Santhosh (Chemical Communications, 2022)
Solvent-free organic liquids are well-known for their excellent luminescence features. Hence, the recent developments in this area have marked them as potential emitters with high quantum yield and enhanced processability. The support of an available liquid matrix enables doping to deliver hybrid liquids with intriguing luminescence features. In this direction, we report solvent-free liquid donor-acceptor pairs with exciplex emission and room temperature phosphorescence at very low acceptor loading. The underlying weak intermolecular interactions have been revealed by 2D NMR techniques and theoretical calculations. The formation of large-area thin films by exciplex and phosphorescent liquid hybrids will encourage the development of scalable lighting and display materials.

Thermally activated delayed fluorescent solvent-free organic liquid hybrids for tunable emission applications - Nidhankar, Aakash D. D.; Goudappagouda; Kothavade, Premkumar D.; Dongre, Sangram D.; Veer, Sairam Dnyaneshwar; Dash, Soumya Ranjan; Rajeev, Kavya; Unni, K. N. Narayanan; Shanmuganathan, Kadhiravan; Babu, Sukumaran Santhosh (Chemistry-An Asian Journal, 2023)
The synthetic feasibility and excellent luminescence features of organic molecules attracted much attention and were eventually found useful in lighting applications. In this context, a solvent-free organic liquid having attractive thermally activated delayed fluorescence features in bulk along with high processability has prime importance. Herein, we report a series of naphthalene monoimide-based solvent-free organic liquids exhibiting cyan to red thermally activated delayed fluorescence with luminescence quantum yields up to 80% and lifetimes between 10 to 45 mu s. An effective approach explored energy transfer between liquid donors with various emitters exhibiting tunable emission colors, including white. The high processability of liquid emitters improved the compatibility with polylactic acid and was used for developing multicolor emissive objects using 3D printing. Our demonstration of the thermally activated delayed fluorescence liquid will be much appreciated as a processable alternate emissive material suitable for large-area lighting, display, and related applications.
Keywords: 3D printing; Energy Transfer; OLED; Organic Liquids; TADF